Design And Development Of A Fuzzy Controlled Cooling Uint Integrated With The Industrial Wax Moulding Unit Using Lab View (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The wax moulding plant requires a cooling unit to cool various types of molten paraffin wax into specific sizes to a temperature 50 C above the wax melting point . The presently used systems use a moulding plant which comprises of Wax Precooler section, Wax moulding Unit and a cooling fan Unit. The inefficiency of the existing system employed at CPCL is due to the non uniform cooling of  the wax due to the combined effect of the atmospheric temperature and the unchanging speed of the cooling fan resulting in production and energy loss. The proposed technique exploits the use of a conveyor with variable speed drives and varying cooling fan speed which is implemented with fuzzy logic algorithms using LabVIEW which provides high accuracy and precision. The moulded wax has a variety of applications in lubrication, electrical insulation, food processing industry and in pharmaceutical industry.